Descriptions of unknown sexes, new geographical records, and host associations for two South American species of Megachile (Hymenoptera: Megachilidae) - Durante, Silvana; Torretta, Juan Pablo; Colombo, Maria Guadalupe (Zootaxa, 2014)
The cosmopolitan genus Megachile include many species described on the basis of only one sex. Sexual dimorphism is very pronounced in these taxa and therefore sexes are often difficult to associate, thus making species identification nearly impossible. The females of M. (Chrysosarus) concava and M. (Pseudocentron) variplantis are described and illustrated. Additional geographical and host records are provided as well as comments on their diagnostic features and identification based on existing keys.